Associations between craving, trauma, and the DARNU scale: Dissatisfied, anxious, restless, nervous, and uncomfortable. (3rd September 2017) - Proctor, Steven L.; Llorca, Geoffrey M.; Perez, Patsy K.; Hoffmann, Norman G.
ABSTRACT: This study evaluated the clinical utility of a measure of negative emotionality, the DARNU scale (Dissatisfied, Anxious, Restless, Nervous, and Uncomfortable), using data from a naturalistic sample of consecutive admissions to a residential substance use treatment program. Data derived from routine clinical assessments of 124 (55.6% male) patients were analyzed to assess study aims. The DARNU scale in addition to measures of drug and alcohol craving, severity of posttraumatic stress disorder (PTSD), and severity of substance use disorder (SUD) were administered to all patients. Results revealed significant positive correlations between DARNU and PTSD ( r = .783), craving ( r = .366), and SUD ( r = .331). The DARNU scale yielded a Cronbach's alpha of .91. When patients were categorized into quartiles based on DARNU elevations, 88.9% of patients in the highest quartile met diagnostic criteria for PTSD, while 89.2% of patients in the lowest quartile did not receive a PTSD diagnosis. Linear regression indicated that the affective vulnerability measured by DARNU mediated the relationship between PTSD and craving. The DARNU scale may identify patients at elevated risk for relapse, and may have the potential to serve as a brief clinical indicator of PTSD without asking about a specific traumatic event.